2013
DOI: 10.18832/kp2013018
|View full text |Cite
|
Sign up to set email alerts
|

The dependence of malt quality on the variety and year.

Abstract: Vydává Výzkumný ústav pivovarský a sladařský, a. s. Časopis Kvasný průmysl publikuje původní recenzované vědecké práce, přehledové články, technické a další zprávy a články o historii z oblasti sladařství, pivovarství, nápojů a navazujících oborů. Kvasný průmysl je konspektován v databázích AGRIS, BRI, CAB Abstracts, Chemical Abstracts, České zemědělské a potravinářské bibliografii, FSTA, VITIS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 28 publications
(44 reference statements)
0
3
0
Order By: Relevance
“…In this study, the analysis of variance of the technological parameters found significant differences between C and E in the malting quality index (P = 0.048), relative extract at 45°C (P = 0.003), Kolbach index (P = 0.011), β-glucan in wort (P = 0.013) and colour of malt (P = 0.032) ( Table 2). The most significant differences were found between C and E in the relative extract at 45°C and the β-glucan in wort that are the least affected by locality and year (Dráb et al 2013). The relative extract at 45°C indicates the level of proteolytic modification and it is an important feature especially in Central Europe (Psota & Kosař 2002).…”
Section: Resultsmentioning
confidence: 95%
“…In this study, the analysis of variance of the technological parameters found significant differences between C and E in the malting quality index (P = 0.048), relative extract at 45°C (P = 0.003), Kolbach index (P = 0.011), β-glucan in wort (P = 0.013) and colour of malt (P = 0.032) ( Table 2). The most significant differences were found between C and E in the relative extract at 45°C and the β-glucan in wort that are the least affected by locality and year (Dráb et al 2013). The relative extract at 45°C indicates the level of proteolytic modification and it is an important feature especially in Central Europe (Psota & Kosař 2002).…”
Section: Resultsmentioning
confidence: 95%
“…Since ancient times, barley has had different use-destinations, including use as human food, animal feed, and alcoholic drink production [4]. In particular, barley is the principal cereal for brewing industry [5][6][7][8], where beer is one of the oldest known alcoholic beverages, and is obtained by fermentation of malt wort in the presence of yeast. Beer products were found in pottery dating back at least 9000 years, and brewing is thought to have existed in Egypt 5000 to 7000 years ago [9].…”
Section: Introductionmentioning
confidence: 99%
“…Total kilning time was 22 hours. Pre-kilning was carried out at 55 °C and kilning at 80 °C for 4 hours (Dráb et al, 2013).…”
Section: Micromaltingmentioning
confidence: 99%